79.5k views
1 vote
Given f(x)=(x-6)^2+7 find f^-1(x) then state whether f^-1(x) is a function

Given f(x)=(x-6)^2+7 find f^-1(x) then state whether f^-1(x) is a function-example-1

1 Answer

2 votes

For this case we must find the inverse of the following function:


f (x) = (x-6) ^ 2 + 7

For this we follow the steps below:

Replace f (x) with y:


y = (x-6) ^ 2 + 7

We exchange the variables:


x = (y-6) ^ 2 + 7

We solve the equation for "y", that is, we clear "y":


(y-6) ^ 2 + 7 = x

We subtract 7 on both sides of the equation:


(y-6) ^ 2 = x-7

We apply square root on both sides of the equation to eliminate the exponent:


y-6 = \sqrt {x-7}

We add 6 to both sides of the equation:


y = \pm \sqrt {x-7} +6

We change y by
f ^ {- 1} (x):


f ^ {- 1} (x) = \pm \sqrt {x-7} +6

Answer;


f ^ {- 1} (x) = \pm \sqrt {x-7} +6

If it is a inverse function.

User Saxos
by
5.0k points